The Ship of secrets : the tenth adventure in the kingdom of fantasy - Stilton, Geronimo (New York, NY : Scholastic Inc., 2016)
On his way to the Grand Masked Ball and what promises to be a disaster of a date, Geronimo is once again whisked away to the Kingdom of Fantasy, and this time he must save the Princess of the Vanilla Fairies from an evil wizard who is using the pirate ship, Ship of Secrets, to gather magical objects to increase his power and take over the kingdom.
Keywords: Children's fiction; Adventure and adventurers -- fiction